Reduced Treatment Sensitivity of SARS-CoV-2 After Multigenerational Human-to-Human Transmission - Wang, Qiang; Yang, Tong; Wang, Yang (Frontiers in Physics, 2020)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has become a rapidly spreading worldwide pandemic, seriously threatening global public health security. At present, there is still no vaccine or specific drug available for the virus. Therefore, epidemiological prevention and control is crucial to block further spread of the disease. In this present study, based on the public information of COVID-19 in Qingdao, Shandong Province, China, we analyzed the epidemiological characteristics and treatment effects of 60 confirmed cases. It was revealed that the hospital stay of patients were imported from Wuhan or infected by Wuhan patients was obviously shorter than that of those who were imported from other regions or infected by them. In addition, in Hubei-related patients, the earlier transmission generation, which refers to the imported patients (G0) and the first-generation infections (G1), was associated with reduced cure time. Therefore, we speculated that the treatment sensitivity of SARS-CoV-2 decreased within interpersonal transmission in the early stage of this epidemic.